Studies on Novel Diagnostic and Predictive Biomarkers of Intrahepatic Cholestasis of Pregnancy Through Metabolomics and Proteomics - Dong, Ruirui; Ye, Ningzhen; Zhao, Shaojie; Wang, Gaoying; Zhang, Yan; Wang, Tiejun; Zou, Ping; Wang, Jing; Yao, Tingting; Chen, Minjian; Zhou, Conghua; Zhang, Ting; et al. (Frontiers in Immunology, 2021)
Background: Intrahepatic cholestasis of pregnancy (ICP) usually occurs in the third trimester and is associated with increased risks in fetal complications. Currently, the exact mechanism of this disease is unknown. The purpose of this study was to develop potential biomarkers for the diagnosis and prediction of ICP. Methods: We enrolled 40 pregnant women diagnosed with ICP and 40 healthy pregnant controls. The number of placental samples and serum samples between the two groups was 10 and 40 respectively. Ultra-performance liquid chromatography tandem high-resolution mass spectrometry was used to analyze placental metabolomics. Then, we verified the differentially expressed proteins and metabolites, both placental and blood serum, in the first, second, and third trimesters. Results: Metabolomic analysis of placental tissue revealed that fatty acid metabolism and primary bile acid biosynthesis were enriched. In the integrated proteomic and metabolomic analysis of placental tissue, peroxisomal acyl-CoA oxidase 1 (ACOX1), L-palmitoylcarnitine, and glycocholic acid were found to be three potential biomarkers. In a follow–up analysis, expression levels of both placental and serum ACOX1, L-palmitoylcarnitine, and glycocholic acid in both placenta and serum were found to be significantly higher in third-trimester ICP patients; the areas under the ROC curves were 0.823, 0.896, and 0.985, respectively. Expression levels of serum ACOX1, L-palmitoylcarnitine, and glycocholic acid were also significantly higher in first- and second-trimester ICP patients; the areas under the ROC curves were 0.726, 0.657, and 0.686 in the first trimester and 0.718, 0.727, and 0.670 in the second trimester, respectively. Together, levels of the three aforementioned biomarkers increased the value for diagnosing and predicting ICP (AUC: 0.993 for the third, 0.891 for the second, and 0.932 for the first trimesters). Conclusions: L-palmitoylcarnitine, ACOX1, and glycocholic acid levels taken together may serve as a new biomarker set for the diagnosis and prediction of ICP.